Recycling of metallurgical wastes in ceramics: A sustainable approach - Er, Yusuf; Sutcu, Mucahit; Gencel, Osman; Totic, Ermedin; Erdogmus, Ertugrul; Cay, Vedat Veli; Kazmi, Syed Minhaj Saleem (Elsevier Sci Ltd, 2022)
This pioneering study focuses on the production, testing, and comparative assessment of iron-rich metallurgical wastes, including copper slag (CS), rolling mill scale (RMS), and ferrous-metal grinding dust (FGD), incorporated fired clay bricks. For this purpose, the fired clay bricks incorporating CS, FGD, and RMS are prepared considering three different dosages of wastes (i.e., 10 %, 20 %, and 30 % of the weight of clay) and fired at two different temperatures (i.e., 900 degrees C and 1000 degrees C). Various tests were performed to examine different physical, mechanical, durability, and leaching characteristics of bricks. Results show increased porosity and loss-on-ignition of brick samples with increased CS dosage. However, decreased apparent porosity and loss-on-ignition of brick samples are observed with the increased dosages of RMS and FGD. All the brick samples incorporating metallurgical wastes satisfy the compressive strength and water absorption requirements as per ASTM C62 and other building standards. Scanning electron microscopy shows homogeneous and dense microstructures for brick samples incorporating 30 % RMS and FGD dosages. For all the brick samples fired at 1000 degrees C, amounts of heavy metals in the leachates are detected well below the Environmental Protection Agency specified limits. Based on the results, recycling of CS, RMS, and FGD in brick manufacturing is an attractive solution to avoid environmental issues related to landfilling of hazardous wastes and achieve efficient waste management.
Keywords: Ceramics; Metallurgical wastes; Sustainability; Recycling; Building materials